2014
DOI: 10.1111/ctr.12323
|View full text |Cite
|
Sign up to set email alerts
|

Travel for transplantation and transplant commercialism in Argentina: a 4‐decade experience from a University Hospital

Abstract: Travel for transplantation and transplant commercialism have become major issues in the last years, generating a passionate medical, legal, and ethical debate. We evaluated the general characteristics of patients who received a kidney transplant abroad and were subsequently followed in our institution. Then, we carried out a retrospective analysis of travelers' outcomes and compared them with a matched cohort of patients transplanted in our center. Between 1971 and 2008, 58 kidney transplants were performed ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…6 The Internet was the primary source tourists use to initially learn a potential destination country followed by word-ofmouth and peer-support networks. 6,8,9,15,16,18,19,34,35 Many factors drove the decision making about the destination. Drinkert and Singh 6 reported that 30.8% of medical tourists adopted physician's advice followed by word-ofmouth (26.2%) and the Internet (13.5%) to decide on the destination hospital.…”
Section: Information Sources and Decision Making For Medical Tourismmentioning
confidence: 99%
“…6 The Internet was the primary source tourists use to initially learn a potential destination country followed by word-ofmouth and peer-support networks. 6,8,9,15,16,18,19,34,35 Many factors drove the decision making about the destination. Drinkert and Singh 6 reported that 30.8% of medical tourists adopted physician's advice followed by word-ofmouth (26.2%) and the Internet (13.5%) to decide on the destination hospital.…”
Section: Information Sources and Decision Making For Medical Tourismmentioning
confidence: 99%
“…Most patients traveled for kidney transplants, the majority of which were living unrelated . Patients also traveled for liver transplants .…”
Section: Resultsmentioning
confidence: 99%